Training in Water Chlorination to Prevent Diarrheal Diseases in Rural Communities of Mexico - Hernández, Armando Pacheco; Vargas, Carisma Monserrat Meyer (Darul Yasin Al Sys, 2025)
This study addresses the crucial role of water chlorination training as a strategy to reduce the incidence of diarrheal diseases in rural communities, specifically in the health jurisdiction of Zacualtipán de Ángeles, Hidalgo, Mexico. The research employed a quasi-experimental design involving 200 households and 50 healthcare workers, divided into intervention and control groups. Participants in the intervention group underwent a structured training program focusing on water chlorination techniques, education on waterborne disease prevention, and monitoring practices. Data collection involved pre- and post-intervention surveys, water quality sampling, and diarrheal disease incidence monitoring. Statistical analysis showed a 40% reduction in diarrheal cases in the intervention group, with a significant improvement in technical knowledge and practical application of chlorination procedures. These findings highlight the effectiveness of community-based and participatory training interventions in enhancing public health outcomes in rural settings. The study also identifies challenges, such as limited resources and high staff turnover, that could hinder long-term sustainability. It concludes with a call for continuous training programs and accessible water monitoring systems to ensure consistent water quality. The research contributes to both theoretical discussions on public health education and practical frameworks for implementing low-cost, high-impact interventions in underserved communities.